The Impact of the Ras Shamra Texts on the Study of the Songs of Songs - Schoville, Keith Norman
Dissertation; Supervisor: M. Mansoor; Microfilm $4.00; Xerox $6.80. Cf. Dissertation Abstracts 31 (1970) 2755-A.